Enzyme-Linked Aptamer Assay (ELAA) for Detection of Toxoplasma ROP18 Protein in Human Serum - Vargas-Montes, Monica; Cardona, Nestor; Moncada, Diego Mauricio; Molina, Diego Alejandro; Zhang, Yang; Gómez-Marín, Jorge Enrique (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii engenders the common parasitic disease toxoplasmosis in almost all warm-blooded animals. Being a critical secretory protein, ROP18 is a major virulence factor of Toxoplasma. There are no reports about ROP18 detection in human serum samples with different clinical manifestations. New aptamers against ROP18 protein were developed through Systematic Evolution of Ligands by Exponential enrichment (SELEX). An Enzyme-Linked Aptamer Assay (ELAA) platform was developed using SELEX-derived aptamers, namely AP001 and AP002. The ELAA was used to evaluate total antigen from T. gondii RH strain (RH Ag) and recombinant protein of ROP18 (rROP18). The results showed that the ELAA presented higher affinity and specificity to RH Ag and rROP18, compared to negative controls. Detection limit of rROP18 protein in serum samples was measured by standard addition method, achieving a lower concentration of 1.56 μg/mL. Moreover, 62 seropositive samples with different clinical manifestations of toxoplasmosis and 20 seronegative samples were tested. A significant association between ELAA test positive for human serum samples and severe congenital toxoplasmosis was found (p = 0.006). Development and testing of aptamers-based assays opens a window for low-cost and rapid tests looking for biomarkers and improves our understanding about the role of ROP18 protein on the pathogenesis of human toxoplasmosis.